Liquidity, Profitability, and Cash Holding on Firm Value in the Bank Sub-Industry - Amelia Suhada; Darto (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of Liquidity, Profitability, and Cash Holding on Firm Value in the banking sub-industry listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. Independent variables in this study include Liquidity as measured by Loan to Deposit Ratio (LDR), Profitability as measured by Return on Equity (ROE), and Cash Holding as measured by Cash & Cash Equivalents to Total Assets. Meanwhile, Firm Value as the dependent variable is measured by Tobin's Q ratio. The research method used is a quantitative approach with secondary data obtained from the financial statements of banking companies listed on the IDX during the study period. The data analysis technique used is panel data regression with statistical software to test the relationship between variables. The results showed that Liquidity has an insignificant positive effect on Firm Value. Profitability also has an insignificant positive effect on Firm Value, which indicates that an increase in company profits has an impact on increasing investor confidence. Meanwhile, Cash Holding has a significant positive effect on Firm Value, which indicates that companies that hold large amounts of cash tend to have lower firm value, because investors prefer companies that allocate their cash for productive investment.